A clinical case of physical therapy of a child with multiple sulfatase deficiency - Grygus , I.M.; Nagorna , O.B.; Nesterchuk , N.E.; Nogas , A.O.; Podoliaka , P.S.; Gamma , T.V. (Medicni Perspektivi, 2021)
The article deals with the problems of physical therapy in children with multiple sulfatase deficiency (MSD). The purpose of the study presented in the article was to substantiate the need to form a structured, personalized comprehensive rehabilitation program for children with multiple sulfatase deficiency. The objectives of the study were to analyze the literature on the topic of the study, to study the clinical phenotype of multiple sulfatase deficiency and potential complications of this pathology, to justify the use of physical therapy in children with multiple sulfatase deficiency. Research methods: analysis of scientific and methodological sources of domestic and foreign authors, pedagogical observation, collection of anamnestic information of the patient. The publication discusses the clinical phenotype of genetic pathology and possible potential complications of this orphan disease, strategic vectors of an individual rehabilitation program. The description of a clinical case of late infantile form of the disease is presented. The effectiveness of a six-months’ implementation of the physical therapy program is being investigated. For rehabilitation examination of children with MSD, it is proposed to use testing of children with psychomotor disorders. The technique of massage, the appropriateness of verticalization and orthotics, sensory enrichment of the environment of a child with this genetic pathology are revealed. Exercises of therapeutic physical culture are proposed, they will help to maintain postural control, support ability and functioning of arms, legs, hand-eye coordination, and help prevent diseases of the bronchopulmonary system. It is noted that MSD has been insufficiently studied not only from the standpoint of a treatment strategy, diagnostic algorithms for clinical multisystem manifestations, but also requires attention to analyze the effectiveness and efficiency of the system of modern rehabilitation technologies for children with this diagnosis.